Modulation of Muscle Synergies in Lower-Limb Muscles Associated With Split-Belt Locomotor Adaptation - Oshima, Atsushi; Nakamura, Yasuo; Kamibayashi, Kiyotaka (Frontiers in Human Neuroscience, 2022)
Humans have great locomotor adaptability to environmental demands, which has been investigated using a split-belt treadmill with belts on both the left and right sides. Thus far, neuromuscular control in split-belt locomotor adaptation has been evaluated by analyzing muscle activities at the individual muscle level. Meanwhile, in the motor control field, the muscle synergy concept has been proposed. Muscle synergies are considered the fundamental building blocks of movement and are groups of coactive muscles and time-varying activation patterns, thereby, reflecting the neurophysiological characteristics of movement. To date, it remains unclear how such muscle synergies change during the adaptation and de-adaptation processes on the split-belt treadmill. Hence, we chronologically extracted muscle synergies while walking on the split-belt treadmill and examined changes in the number, muscle weightings, and temporal activation patterns of muscle synergies. Twelve healthy young males participated, and surface electromyography (EMG) signals were recorded bilaterally from 13 lower-limb muscles. Muscle synergies were extracted by applying non-negative matrix factorization to the EMG data of each leg. We found that during split-belt walking, the number of synergies in the slow leg increased while an extra synergy appeared and disappeared in the fast leg. Additionally, the areas under the temporal activation patterns in several synergies in both legs decreased. When both belts returned to the same speed, a decrease in the number of synergies and an increase in the areas under the temporal activation patterns of several synergies were temporally shown in each leg. Subsequently, the number of synergies and the areas under the temporal activation patterns returned to those of normal walking before split-belt walking. Thus, changes in the number, muscle weightings, and temporal activation patterns of synergies were noted in the split-belt locomotor adaptation, suggesting that the adaptation and de-adaptation occurred at the muscle synergy level.